1996
DOI: 10.1046/j.1365-3024.1996.d01-94.x
|View full text |Cite
|
Sign up to set email alerts
|

In situ characterization of leucocyte subpopulations after infection with Eimeria tenella in chickens

Abstract: We characterized the leucocyte subpopulations after infection with Eimeria tenella in both naive and immune chickens. Immunocytochemical staining was used to characterize the cells in situ, so that the interaction between host and parasite could be studied. More leucocytes were detected in the lamina propria of immune chickens, and leucocytes infiltrated the ceca more rapidly than in naive chickens, but the infiltration was less pronounced than in naive chickens. In naive chickens, most infiltrated leucocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
5

Year Published

2000
2000
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 30 publications
6
47
5
Order By: Relevance
“…The inflammation observed in Eimeria-infected intestine is associated with an infiltration of macrophages and T cells (38), accompanied by edema and a thickening of the mucosa (27). IL-1␤ is a powerful proinflammatory cytokine secreted by many different cell types, with stimulated macrophages being the main producer.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammation observed in Eimeria-infected intestine is associated with an infiltration of macrophages and T cells (38), accompanied by edema and a thickening of the mucosa (27). IL-1␤ is a powerful proinflammatory cytokine secreted by many different cell types, with stimulated macrophages being the main producer.…”
Section: Discussionmentioning
confidence: 99%
“…Eimeria infections induce changes in the intestinal intraepithelial population (7,23). Growth of the parasite in the intestinal epithelium leads to the development of the host immune response and CD8 ϩ cells, which increased in number after challenge infection, seem to act as effector cells in acquired immunity (93).…”
Section: Iel and Infectionmentioning
confidence: 99%
“…Several investigations have indicated that cecal tonsil lymphocytes may be involved in the intestinal immune response to Eimeria. For example, during E. tenella infection, an increased number of leukocytes (43) and lymphoid nodules were found in the base of cecal tonsils, accumulating as dense aggregates of lymphocytes containing irregularly scattered lymphoid tissues and germinal centers (8). Cecal tonsil lymphocytes exhibit considerable heterogeneity in surface phenotype and presumably in function (22).…”
Section: Cd8mentioning
confidence: 99%